THE STRENGTH OF THEOLOGICAL FOUNDATION AND MUHAMMADIYAH MOVEMENTS IN FACING THE CHALLENGES OF THE TIMES - Tobroni Tobroni; Asnath Naftali Remtulla (SOSIOEDUKASI, 2025)
This paper will analyze the theological foundations of the development paradigm of Muhammadiyah in Indonesia with reference to three interconnected theological frameworks which include the theology of development, transformative theology and Al-Maun theology. Muhammadiyah, being one of the largest Islamic reform movements in the world, stands out as a special case as it has been able to integrate Islamic theology with modernism models of social change, making it one of the unique models of faith-based development, both spiritual and material aspects of human flourishing. This paper examines how these theological views influence the vast mass of educational institutions, medical care centers, and social welfare programs run by Muhammadiyah and how they carry out practical insights into divine command as expressed in social action and empowerment of the community.